Perbedaan Media Charta Dengan Media Audio Visual Terhadap Hasil Belajar Ipa Biologi Pada Pokok Bahasan Struktur Dan Fungsi Jaringan Tumbuhan Siswa Kelas VIII Smp Muhammadiyah 4 Surakarta Semester Genap Tahun Ajaran 2015/2016 - Ardiasari, Kiki; , Dr. Sofyan Anif, M.Si (2016)
The aim of this research paper is to get to know difference of using audio visual and chart media towards the learning outcomes in biology on thee basis structural discussion and plantation function of students in VIII SMP Muhammadiyah 4 Surakarta academic year 2015/2016. The type of this research is to describe the quantitative approach done through true experiments. The population of research of students VIII even semester consists of six classes in SMP Muhammadiyah 4 Surakarta year 2015/2016. The samples of this research are three classes. The sample of data collection is done through random sampling. The techniques of collecting data are observation, documentation, and test. The data analysis is using variant analysis of one way anova. Learning outcomes in biology student to use audio visual media average student score 80,7, learning outcomes to use chart media average student scores 72,7, and learning outcomes to use control media average student scores 64, after do one way anava test and Post Hoc Test use LSD (Least Significant Difference) the final result show that there are difference of using audio visual and chart media towards the learning outcomes in biology are learning to use audio visual media is the best.